Molecular typing of Dengue virus circulating in Kuching district of Sarawak, Malaysian Borneo, from 2014 to2016 - Lim, M.W.H.; Bong, K.K.; Wong, J.S.; Tchong, F.L.; Ooi, Mong How; Perera, David (Elsevier Inc., 2020)
: Dengue fever is endemic to Malaysia and the past five years has seen a large increase in recorded dengue cases. All four dengue serotypes have been recorded in Malaysia and the state of Sarawak. Historically for Sarawak, DENV-1 and DENV-2 were first serologically detected in 1962, while DENV-3 and DENV-4 were picked up by PCR and Sanger sequencing in 1997–1999. However,no serotype sequence data for Sarawak has been published in recent years.